Edukasi Kewirausahaan UMKM Melalui Platfrom Digital: Entrepreneurship Small And Medium Micro Through Digital Platforms - Ulin Nihayah; Yunita Anisatuzzuhriya; Muhammad Aniq Al Faruqi; Amalia Sania Salsabila (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
In this disruptive era, there are many innovations stand in support entrepreneurship activities, one of which is the digital platfrom development for product marketing. Given the social cultural conditions of today's society, which can almost entirely shop online, are making it increasingly possible for businesses to expand markets.But unfortunately, marketing of entrepreneurial products is still mostly done in conventional ways, for example in businesses located in Pancur Village, Mayong District, Jepara Regency which are engaged in convection businesses. So that many people in general do not know about these products. This can affect the development of the entrepreneurial product itself. This lack of training in using the marketpalce as a place of sale and marketing is what motivated the UIN Walisongo KKN TEAM group 84 to provide education, assistance and monitoring the use of one of the digital platforms, namely the Facebook marketplace, where the Facebook application itself is well known to many people. The purpose of this service activity is to empower the community, especially for students who become entrepreneurs independently in reaching a wider market. The method used in this research is participatory action research (PAR) where the approach in this method is to see, hear and also to understand social phenomena that exist in society. The focus in this research is to provide entrepreneurship education using digital platforms to business actors. This activity contains material on the introduction of digital platforms, planning market predictions to sorting expeditions in product delivery. The result of this education is that it can increase income and new knowledge for business actors in developing the marketing sector Pada era disrupsi ini banyak munculnya inovasi yang mendukung kegiatan kewirausahaan salah satunya yaitu pengembangan platfrom digital untuk pemasaran produk. Didukung dengan kondisi sosial budaya masyarakat sekarang yang hampir keseluruhan dapat berbelanja online,semakin membuka peluang bagi pelaku usaha untuk memperluas pasar. Namun sayangnya pemasaran produk wirausaha masih banyak dilakukan dengan cara konvensional misalnya pada usaha yang berada di Desa Pancur, Kecamatan Mayong, Kabupaten Jepara yang bergerak pada usaha konveksi. sehingga banyak masyarakat umum kurang mengetahui produk tersebut. Hal tersebut dapat mempengaruhi perkembangan produk hasil wirausaha itu sendiri. Kurangnya pelatiahan dalam menggunakan marketpalce sebagai tempat penjualan dan pemasaran inilah yang melatarbelakangi TIM KKN UIN Walisongo kelompok 84 untuk melakukan edukasi, pendampingan dan monitoring penggunaan salah satu platfrom digital yaitu facebook marketplace, dimana aplikasi Facebook sendiri sudah dikenal banyak masyarkat. Tujuan dari kegiatan pengabdian ini yaitu untuk memberdayakan masyarakat khususnya bagi pelajar yang menjadi pelaku wirausaha secara mandiri dalam menjangkau pasar yang lebih luas. Metode yang digunakan dalam penelitian ini adalah participatory action research (PAR) dimana pendekatan dalam metode ini adalah untuk melihat, mendengar dan juga untuk memahami gejala sosial yang ada di dalam masyarakat. fokus dalam penelitian ini untuk memberikan edukasi kewirausahaan menggunakan platform digital kepada pelaku usaha. Kegiatan ini berisi materi tentang pengenalan platfrom digital,perencanaan prediksi pasar hingga pemilahan ekspedisi dalam pengiriman produk. Hasil dari edukasi ini yaitu dapat menambah pendapatan dan pengetahuan baru bagi pelaku usaha dalam mengembangkan sektor pemasaran